Male Sex Associated with Increased Long-term Cardiovascular Mortality after Peripheral Vascular Surgery for Atherosclerosis Despite Optimal Medical Treatment. Issue 6 (December 2015) - Budtz-Lilly, J.W.; Petersen, C.N.; Pedersen, T.F.; Eldrup, N.
Abstract : Background: The cardiovascular burden and consequences of peripheral atherosclerosis appear to differ between men and women. Data regarding long-term outcomes, including the impact of medical prophylactic treatment, are insufficient. This study examined long-term outcomes according to sex following primary vascular surgery, adjusted for multiple variables as well as recommended medical prophylaxis. Methods: All Danish patients who underwent peripheral vascular surgery from January 2000 to December 2007 were stratified into five procedural groups: (a) aorto-iliac bypass or thromboendarterectomy, (b) femoro–femoral crossover, (c) thromboendarterectomy of the femoral arteries, (d) infrainguinal bypass, or (e) axillo- uni-, and bifemoral bypass. Data were analyzed according to sex for differences in myocardial infarction, stroke, and death, individually and combined, after surgery. Results: A total of 11, 234 patients were included: 6, 289 males and 4, 945 females. The overall adjusted hazard ratio for male patients compared with female patients for death was 1.11 (95% CI 1.06–1.17), for MI was 1.16 (95% CI 1.04–1.29), for stroke was 0.99 (95% CI 0.89–1.11), and for any major adverse cardiovascular event was 1.10 (95% CI 1.05–1.16). Conclusions: These findings show that, despite indication, severity, and concomitant medical treatment of peripheral artery disease, men have a higher risk of mortality and adverse cardiovascular events following surgery for peripheral arterial disease.